2021
DOI: 10.1111/ijcp.14334
|View full text |Cite
|
Sign up to set email alerts
|

Saffron improves life and sleep quality, glycaemic status, lipid profile and liver function in diabetic patients: A double‐blind, placebo‐controlled, randomised clinical trial

Abstract: Background: Type 2 diabetes (T2D) is a metabolic disorder that is related to hyperglycaemia, hyperlipidaemia and liver dysfunction and has detrimental effects on a patient's mental health. Hence, the current study investigated the effects of saffron supplementation on dietary intake, anthropometric measures, mood, sleep quality and metabolic biomarkers in overweight/obese patients with T2D.Methods: In a double-blind, randomised controlled trial, 70 overweight/obese patients with T2D were randomly allocated to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 43 publications
0
64
0
Order By: Relevance
“…We included 8 studies with 431 participants [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Table 1 ). One study was reported in two reports (Lopresti et al, 2020; Lopresti et al, 2021) and was referred to as Lopresti et al, (2021).…”
Section: Resultsmentioning
confidence: 99%
“…We included 8 studies with 431 participants [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ] ( Table 1 ). One study was reported in two reports (Lopresti et al, 2020; Lopresti et al, 2021) and was referred to as Lopresti et al, (2021).…”
Section: Resultsmentioning
confidence: 99%
“…Current, anti‐diabetic therapeutic approaches have targeted both optimal glycemic control and reduced cardiovascular risk (Siasos et al, 2020). Contrary to a plethora of animal studies, robust evidence supporting the hypoglycemic effects of saffron is lacking in humans, since this is documented only in a few randomized clinical studies (Milajerdi et al, 2018; Aleali et al, 2019; Tajaddini et al, 2021). Recently, a meta‐analysis enrolled nine randomized trials assessing the hypoglycemic effects of saffron or crocin (Rahmani et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…Based on a meta-analysis of 23 trials, it was demonstrated that saffron at a dose of 28 to 30 mg daily had positive effects on anxiety and depressive symptoms in adults with major depressive disorder and adults experiencing depressive symptoms [ 4 ]. At similar doses, saffron has also been shown to have mood-enhancing effects in peri-menopausal women [ 5 ], youth experiencing depressive and anxiety symptoms [ 6 ], adults with diabetes [ 7 ], and adults with metabolic syndrome [ 8 ]. It also has demonstrated positive effects on sleep quality in adults experiencing poor sleep [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%